PELATIHAN KESIAPSIAGAAN BENCANA PADA SISWA SD MELALUI PERMAINAN EDUKATIF “AKSANA” - Yessy Elita; Rita Sinthia; Mona Ardina (Universitas Bengkulu, 2019)
Bengkulu Province is an area located on three tectonic plates namely Indo-Australia, Eurasia, and Pacific which contain potential natural disasters such as earthquakes and tsunamis. Therefore, it is very important to prepare the community to be prepared for the disaster, including children. In every event of a disaster, there are many victims of children. Providing of knowledge and skills will minimize loss of life. Considering the importance of disaster preparedness, disaster preparedness training activities are carried out through educative games “AKSANA”. The word of AKSANA means Anak Sadar Bencana. This disaster preparedness training was attended by 30 students of SDN I Kota Bengkulu. School selection based on high level of disaster potential. SDN I is surrounded by beaches and is in the lowlands with a distance of less than 1 km from the beach. The service method is through AKSANA games consisting of disaster ladder snake, crosswords, and playbook about a disaster. In this activity, it was equipped with a simulation of self-rescue during an earthquake at the school accompanied by the PMI of Bengkulu Province. The effectiveness of disaster preparedness training in elementary school children was indicated by a significant increase in the pre-test and post-test scores from the average category (6.4) to high (8.9). With the increase in test scores, it shows that disaster preparedness training through AKSANA games can improve the knowledge and skills of students of SDN 1 Kota Bengkulu in dealing with natural disasters.